Jordan higher derivations in prime ?-rings (Bangladesh Journal of Scientific Research, 2016)
The objective of this paper is to study Jordan higher derivations in prime ? -rings. We introduce a higher derivation and a Jordan higher derivation in ? -rings. For a 2-torsion free prime ? -ring M which satisfies the condition a?b?c = a?b?c for all a,b, c?M and ? ,? ?? , we prove that every Jordan higher derivation D = (di)i?N0 of M is a higher derivation of M Bangladesh J. Sci. Res. 27(2): 155-163, December-2014